The Influence of Conductive Salt Ion Selection on EDLC Electrolyte Characteristics and Carbon-Electrolyte Interaction. Issue 5 (16th January 2015) - Pohlmann, S.; Ramirez-Castro, C.; Balducci, A.
Abstract : This study compares several electrolytes for application in electrochemical double layer capacitors (EDLCs), as well as their influence on double layer formation on different activated carbon materials. While propylene carbonate (PC) was used as electrolyte solvent in all cases, the applied conductive salt was varied. A change in conductive salt was found to have a great impact on solubility as well as the electrolytes' ion transport properties. Most importantly the choice of conductive salt strongly influenced the maximum operative potentials of PC based electrolytes, leading to EDLCs exhibiting maximum operative voltages as high as 3.5 V. Furthermore it was found that not only a high operative voltage, but also well adjusted transport properties are needed for an EDLC electrolyte in order to maximize the device's energy and power capabilities. Finally the electrolytes' influence on the capacitance of five activated carbon materials was studied, leading to the conclusion that in order to maximize energy storage in EDLCs, electrolyte and carbon material have to be adjusted one to another.